Digital Leadership of School Administrators under Rayong Primary Educational Service Area Office 1, Pluak Daeng District School Group - สัญญาลักษ์ จิรศักดิ์; การีเวท สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the digital leadership of school administrators, 2) to compare the digital leadership of school administrators classified by status, age, work experience, and school size, and 3) to be guidelines for developing digital leadership of school administrators. The research methodology used a quantitative approach. The sample consisted of 234 school administrators and teachers in the academic year 2025, obtained through Krejcie & Morgan’s table, proportional stratified random sampling, and simple random sampling and Interview Form. The instrument was a 5-rating scale questionnaire with a reliability of 0.840. Statistics used were mean, standard deviation, and One-Way Analysis of Variance (One-Way ANOVA) and Thematic Analysis. The results showed that: 1. The overall digital leadership of school administrators was at the highest level. When considering each aspect, it was found that the aspect with the highest mean score was digital communication and networking at the highest level, while management and application of digital technology had the lowest mean score at a high level. 2. When comparing digital leadership classified by status and age, statistical analysis revealed significant differences at the .05 level. However, no significant differences were found when classified by work experience and school size. 3. The guidelines for developing digital leadership of school administrators found that developing digital leadership should focus on driving through digital technology coupled with organizational culture in 5 key areas: digital vision and strategy focusing on Digital First policy, management focusing on data-driven decision making, promoting digital culture focusing on creating safe spaces, digital communication focusing on proactive communication, and ethics and cybersecurity focusing on being a role model in complying with PDPA laws to build strong digital immunity.